Digital holographic inspection system for the inner surface of a straight pipe. (October 2017) - Yokota, Masayuki; Koyama, Teppei; Takeda, Kazufumi
Highlights: Digital holographic inspection system for a straight pipe is proposed. New signal processing using pattern matching is applied to correct height profile. Color image and surface profile of the inner wall are used for the inspection. Abstract: A multicolor digital holographic inspection system achieving both automatic scanning sensing head and automatic correction of a distortion in the profile due to positional error of a sensing head has been applied to the inner surface of a straight brass pipe having artificial defects on its wall. To investigate the inner surface of the pipe, the sensing head consisting of a cone-shaped mirror (CSM) glued to an aluminum base in the pipe is illuminated by the collimated RGB laser beams from the outside of the pipe. In the system, by changing the wavelength of the illumination light and scanning the CSM in the pipe, data acquisitions and analysis are performed using a personal computer. It is shown that the pipe inspection, including a classification of defects, can be successfully conducted by comparing the multicolor intensity images and the height profile of inner surface of pipe.